Association between the peripheral neutrophil-to-lymphocyte ratio and metabolic dysfunction-associated steatotic liver disease in patients with type 2 diabetes - Zhu, Nan; Song, Yongfeng; Zhang, Chen; Wang, Kai; Han, Junming (Frontiers in Medicine, 2023)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) and type 2 diabetes frequently co-occur, imposing a tremendous medical burden. A convenient and effective MASLD indicator will be beneficial to the early diagnosis of disease. In the clinical laboratory, the neutrophil-to-lymphocyte ratio (NLR) is a readily accessible hematological marker. This study designed to determine the relation between the NLR and MASLD in type 2 diabetes patients. Methods: Data from 1151 type 2 diabetes inpatients without infections, malignancy or hematological diseases who were recruited from 2016 through 2022 were analyzed in the retrospective study. The patients were stratified into NLR tertiles (total population: high NLR level>2.18; middle NLR level: 1.58-2.18; low NLR level<1.58), with additional subgroup stratification by sex (men: high NLR level>2.21; middle NLR level: 1.60-2.21; and low NLR level<1.60; women: high NLR level>2.12; middle NLR level: 1.53-2.12; and low NLR level<1.53). After adjusting for confounders (age, sex, weight, Glu, ALT and TG) associated with MASLD, the odds ratio (OR) and the corresponding 95% confidence interval (CI) of the NLR were obtained by using a binary logistic regression analysis to verify the correlation between the NLR and MASLD. Results: Compared to non-MASLD patients, MASLD patients had higher weight, blood glucose, insulin and C-peptide, worse liver function (higher ALT and GGT), lower HDL (all P<0.05), and lower NLR (P<0.001). The prevalence of MASLD was 43.75% (high NLR level), 55.21% (middle NLR level) and 52.22% (low NLR level) (P<0.05). Compared to those of the high NLR level, the adjusted ORs and 95% CIs of the middle and low NLR levels were 1.624 (95% CI: 1.141-2.311) and 1.456 (95% CI: 1.025-2.068), for all subjects, while they were 1.640 (95% CI: 1.000-2.689) and 1.685 (95% CI: 1.026-2.766), for men. Conclusions: A low NLR is associated with a greater risk of MASLD.